Pengaruh Citra Perusahaan dan Kualitas Pelayanan LPD terhadap Loyalitas Nasabah Pada Lembaga Perkreditan Desa (LPD) Desa Adat Kesiman, Kecamatan Denpasar Timur, Bali - MANULLANG, RUTH KRISTIN; BUDIASA, I WAYAN; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The Influence of Company Image and Service Quality on Customer Loyalty in The Village Credit Institution (LPD) of Kesiman Traditional Village  in East Denpasar District, Bali A good company image and service quality will create customer satisfaction, which in turn creates customer loyaty. This study aims to investigate the influence of company image and service quality on customer loyalty in the Village Credit Institution (LPD) of Kesiman Traditional Village in East Denpasar District, Bali. The quantitative data were analyzed with the Smart-PLS 3.0 program and the qualitative data were analyzed using descriptive analysis. This research uses accidental sampling method. The sample in this study includes 50 respondents, with a consideration that the number meets the minimum requirement of 30 and the maximum of 100 samples for SEM analysis method through the smart-PLS program. Based on the results of this research, it can be concluded that the company image has a negative and insignificant impact on customer loyalty. The service quality has a positive and significant impact on customer loyalty.